The Effects of Leadership and Motivation on Turnover Intention and Employee Performance of Frontliner Employee at PT. Bank Central Asia, Tbk Main Branch Office Pekanbaru - Kevin Marclinto; Layla Hafni (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aim to determine the effect of leadership style and motivation on turnover intention and frontliner employee performance at PT. Bank Central Asia, Tbk Pekanbaru Main Branch Office. The respondents surveyed were 45 respondents. Analysis of the data used in this study is a path analysis test to analyze the pattern of relationships between variables with the aim of knowing the direct and indirect effects of the independent variables (leadership style and motivation) influencing the dependent variable (turnover intention and employee performance). The results showed leadership style and motivation influence employee turnover intention. Leadership style affects employee performance but motivation does not. Turnover intention does not affect employee performance. This study recommends and recommends for companies to be able to maintain leadership and motivation levels given to employees so that employee performance can be maintained and eliminate the intention of employees to leave the company.